2018
DOI: 10.22271/ortho.2018.v4.i4h.78
|View full text |Cite
|
Sign up to set email alerts
|

Dervan dermatome syndrome often missed but surprisingly common coexistent spine pathology in ‘Knee Pain’, ignore at your own risk

Abstract: Introduction: Knee pain is among the commonest complaints in the outpatient orthopedic department. However the cause does not always originate from knee itself. and knee pain is used by the patient more as an umbrella term. In fact very few patients give the complete list of accompanying symptoms. They have more often than not to be coaxed out of the patient. To make matters more complex, Referred pain from the Spinal nerves, Hip and Ankle joints join the many structures around the knee to make knee pain an um… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…[11][12][13][14][15] . In a previous publication from this institute, on investigation of causes of dissatisfied patients of knee Arthroplasty, it was found that although the patient complained of pain around the knee, the source & pain generator were mostly from the spine 1 . It was thereafter made mandatory for all patients of knee osteoarthritis to undergo spine investigations & detailed clinical examination preoperatively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[11][12][13][14][15] . In a previous publication from this institute, on investigation of causes of dissatisfied patients of knee Arthroplasty, it was found that although the patient complained of pain around the knee, the source & pain generator were mostly from the spine 1 . It was thereafter made mandatory for all patients of knee osteoarthritis to undergo spine investigations & detailed clinical examination preoperatively.…”
Section: Discussionmentioning
confidence: 99%
“…It was thereafter made mandatory for all patients of knee osteoarthritis to undergo spine investigations & detailed clinical examination preoperatively. Furthermore it was found that great concomitant affliction existed between spinal disc disease & knee Osteoarthritis [1] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation